Nδ∗gα-Continuous and Irresolute Functions in Neutrosophic Topological Spaces - K. Damodharan; M. Vigneshwaran; Shuker Khalil (Neutrosophic Sets and Systems, 2020)
In this paper, the notions of Nδ∗gα-continuous and Nδ∗gα-irresolute functions in neutrosophic topological spaces are given. Furthermore, we analyze their characterizations and investigate their properties.